A Conceptual Model for a Cyber-Social-Technological-Cognitive Smart Medium-Size Port - Palominos-Villavicencio, F (Elsevier B.V., 2019)
The medium port currently investigated is incorporating the concept of smart port into decision-making and operational activities. To determine the critical factors that show the existing gaps with those working with Industry 4.0, a systemic conceptual model for a smart medium-size port is designed for a hyperspace containing cyber-social-technological-cognitive domains (CSTC), where are related ideas, perceptions, information and knowledge that should have a highly automated port for efficient management and optimization of logistics processes. A sample of high-level executive experts from three medium ports made it possible to diagnose the CSTC development levels of Chilean ports in each of their domains, detecting gaps with respect to a smart port, identifying opportunities and giving recommendations to reach Industry 4.0 in the near future. © 2020 The Authors. Published by Elsevier B.V.